A population-based study of smoking, serum cotinine and exhaled nitric oxide among asthmatics and a healthy population in the USA. (5th December 2016) - Xu, Xiaohui; Hu, Hui; Kearney, Gregory D.; Kan, Haidong; Carrillo, Genny; Chen, Xinguang
Abstract: Background : Fractional concentration of exhaled nitric oxide (FeNO) is recommended by the American Thoracic Society (ATS) as a noninvasive biomarker of airway inflammation. In addition to inflammation, many factors may be associated with FeNO, particularly tobacco exposure; however, only age has been included as an influential factor for children below 12 years. Numerous studies have demonstrated negative associations between tobacco exposure and FeNO levels with self-reported data, but few with an objective assessment of smoking. Methods : Data from the National Health and Nutrition Examination Survey (NHANES) 2007–2012 were analyzed to examine the association between FeNO and active/passive tobacco. Exposure was assessed by both self-report and serum cotinine levels among 11, 160 subjects aged 6–79 years old with asthma, or without any respiratory disease. Results : Study results indicated 28.8% lower FeNO, 95% CI [25.2%, 32.3%] and 38.1% lower FeNO, 95% CI: [28.1, 46.2] was observed among healthy and asthmatic participants with serum cotinine in the highest quartile compared to those in the lowest quartile, respectively. Self-reported smoking status and recent tobacco use were also associated with decreased FeNO. Self-reported passive smoking was significantly associated with a 1.0% decrease in FeNO 95% CI [0.0, 2.0] among asthmatic subjects but not among healthy subjects. Conclusions : Active smoking, whether measured by self-report or serum cotinine, was associated with decreased FeNO levels. In addition to age, increased attention should be given to tobacco exposure when using FeNO as a biomarker in clinical practice. Additional research is needed to establish reference value of FeNO considering the impact of tobacco exposure.